Chitosan Hydrogels for Chondroitin Sulphate Controlled Release: An Analytical Characterization - Annalisa Bianchera; Enrico Salomi; Matteo Pezzanera; Elisabeth Ruwet; Ruggero Bettini; Lisa Elviri (Journal of Analytical Methods in Chemistry)
This paper provides an analytical characterization of chitosan scaffolds obtained by freeze-gelation toward the uptake and the controlled release of chondroitin sulphate (CS), as cartilage repair agent, under different pH conditions. Scanning electron microscopy (SEM), attenuated total reflectance-Fourier transform infrared spectroscopy (ATR-FTIR), and liquid chromatography-UV spectrophotometry (LC-UV) techniques were exploited to obtain qualitative and quantitative descriptions of polymer and drug behaviour in the biomaterial. As for morphology, SEM analysis allowed the evaluation of scaffold porosity in terms of pore size and distribution both at the surface (Feret diameter 58±19 μm) and on the cross section (Feret diameter 106±51 μm). LC and ATR-FTIR evidenced a pH-dependent CS loading and release behaviour, strongly highlighting the role of electrostatic forces on chitosan/chondroitin sulphate interactions.